The Effect Of Middleman Behavior to Economic Space on TPI Tawang, Gempolsewu Village Rowosari District Kendal Regency - Ardiana Yuli Puspitasari; Yunia Alfianti; Mohammad Agung Ridlo (International Conference on Coastal and Delta Areas, 2017)
Fish Auction Place is an economic space that has great influence for fishermen in marketing their catch so that fishermen can sell their catch as short as possible with good price and can create healthy market through pure auction. Based on Local Regulation of Kendal Regency Number 10 of 2010 concerning management and retribution of fish auction place in Kendal Regency, mention that to guarantee the balance of management of fish auction place in order to improve prosperity and standard of living of fisherman /coastal communities in Kendal District. However, in TPI Tawang area there is a problem that is middleman activity. The activity is very influential on the economic space TPI Tawang. Based on the above problems, the researcher wants to know the influence of behavior middleman to economic space TPI Tawang Gempolsewu Village. To achieve these objectives, several analyzes were conducted, among others, activities of middleman, economic space in TPI Tawang area and analysis of influence of middleman activity on economic space of TPI Tawang community of Gempolsewu Village. In this research using qualitative descriptive approach rationalistic with middleman activity variable and economic space in TPI Tawang area. Stages done in doing this writing is through several stages, among others, preparation, primary or secondary data collection, processing and presentation of data, data analysis, and stage preparation of reports. The conclusion of this research is middleman activity which is in TPI area of Tawang precisely at TPI Tawang dock influence activity in economy room that exist in area of TPI Tawang. The influence of middleman activity in Tawang TPI area can be seen from the activity system which can cause the decrease of activity and the decrease of economic space activity in Tawang TPI area. Keywords: Fish Auction Place, Middleman, Activity, Economy, Coastal, Space